2019
DOI: 10.1094/pdis-06-18-1036-re
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny, Distribution, and Pathogenicity of Lasiodiplodia Species Associated With Cankers and Dieback Symptoms of Persian Lime in Mexico

Abstract: Persian lime (Citrus latifolia Tan.) is an important and widely cultivated fruit crop in several regions of Mexico. In recent years, severe symptoms of gummosis, stem cankers, and dieback were detected in the Persian lime-producing region in the states of Veracruz and Puebla, Mexico. The aims of this study were to identify the species of Lasiodiplodia associated with these symptoms, determine the distribution of these species, and test their pathogenicity and virulence on Persian lime plants. In 2015, symptoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
1
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 53 publications
0
12
1
5
Order By: Relevance
“…Results revealed that L. theobromae was more virulent on lime shoots than other species. In contrast to our results, Bautista-Cruz et al reported that L. theobromae was the least virulent species when inoculated in Persian lime branches [ 70 ]. Several factors differed from the study carried out by Bautista-Cruz et al and might have contributed to the discrepancy between the experiments, including the type of planting material inoculated, the environmental conditions for disease development, the time for virulence assessment, and the fungal strain used in the pathogenicity test.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Results revealed that L. theobromae was more virulent on lime shoots than other species. In contrast to our results, Bautista-Cruz et al reported that L. theobromae was the least virulent species when inoculated in Persian lime branches [ 70 ]. Several factors differed from the study carried out by Bautista-Cruz et al and might have contributed to the discrepancy between the experiments, including the type of planting material inoculated, the environmental conditions for disease development, the time for virulence assessment, and the fungal strain used in the pathogenicity test.…”
Section: Discussioncontrasting
confidence: 99%
“…Several species of Botryosphaeriaceae are known to dieback and branch cankers in Citrus spp. worldwide [ 14 , 20 , 22 , 23 , 66 , 67 , 68 , 69 , 70 ]. Dothiorella viticola has been previously reported to cause gummosis in citrus in California [ 20 ] and Tunisia [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dicha situación se presenta en las zonas productoras de Veracruz, donde se disminuye la vida productiva y producción en árboles de limón 'Persa'. En 2019 se reportó a L. pseudotheobromae, L. theobromae, L. brasiliense, L. subglobosa, L. citricola y L. iraniensis como los agentes causales de la muerte descendente y cancros en huertos comerciales de limón 'Persa' en Puebla y Veracruz (Bautista-Cruz et al, 2019).…”
unclassified
“…In fact, identification of Botryosphaeriaceae using morphology only allows the separation of isolates to the genus level, with DNA phylogeny being the most relevant tool for describing Lasiodiplodia species according to the phylogenetic species concept (Ismail et al 2012;Phillips et al 2013;Slippers et al 2014;Osorio et al 2017). Within Botryosphaeriaceae, the use of DNA sequence data from multiple loci is strongly recommended (Phillips et al 2013;Slippers et al 2014;Rodríguez-Gálvez et al 2017;Rosado et al 2016;Bautista-Cruz et al 2019).…”
mentioning
confidence: 99%